2009
DOI: 10.1111/j.1529-8817.2008.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

LIPID CLASS, CAROTENOID, AND TOXIN DYNAMICS OF KARENIA BREVIS (DINOPHYCEAE) DURING DIEL VERTICAL MIGRATION1

Abstract: The internal lipid, carotenoid, and toxin concentrations of Karenia brevis (C. , <5 lM NO 3 ) mesocosms. Reverse-phase HPLC quantified the epoxidation state (EPS) of the xanthophyll-cycle pigments diadinoxanthin and diatoxanthin, and a Chromarod Iatroscan thin layer chromatography ⁄ flame ionization detection (TLC ⁄ FID) system quantified changes in lipid class concentrations. EPS did not exceed 0.20 in the low-light mesocosm, but increased to 0.65 in the high-light mesocosms. Triacylglycerol and monogalactosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It affords greater protection against grazers and pathogens to compensate for the reduced rates of growth and reproduction. It also provides the cell with a means disposing of unneeded fixed carbon during the onset of nutrient limitation of growth, thereby protecting the photosynthetic electron transport chain from over reduction and attendant oxidative stress [38][40]. The CNB hypothesis predicts a similar increase in cellular PbTx concentrations should also occur under P-limitation.…”
Section: Introductionmentioning
confidence: 99%
“…It affords greater protection against grazers and pathogens to compensate for the reduced rates of growth and reproduction. It also provides the cell with a means disposing of unneeded fixed carbon during the onset of nutrient limitation of growth, thereby protecting the photosynthetic electron transport chain from over reduction and attendant oxidative stress [38][40]. The CNB hypothesis predicts a similar increase in cellular PbTx concentrations should also occur under P-limitation.…”
Section: Introductionmentioning
confidence: 99%
“…6, off-shore cells remain sub-surface because of a higher necessity for nitrogen in oligotrophic nitrogen reduced conditions in the upper water column. Exposure to lower nitrogen concentrations lowers the need for photosynthetic production because essential building blocks containing nitrogen cannot be synthesized (Schaeffer et al, 2009). Reduced availability of nitrogen and carbon fixation under low light led K. brevis to divide at a slower rate as indicated at Step (1) in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Lipid extraction and analysis were previously detailed in Schaeffer et al (2009). Briefly, lipids were analyzed with the MK-V Chromarod-Iatroscan (Iatron, Inc., Tokyo, Japan) thin layer chromatography/flame ionization detection (TLC/FID) system.…”
Section: Biochemistry and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of dinoflagellates have also been observed to undertake vertical migration, residing at the surface during the day and residing at depth at night [19][20][21][22][23]. Although the light intensity at surface water and nutrients at deep water play an important role as drivers of dinoflagellate DVM in laboratory studies [24][25][26][27][28][29][30], recent experiments have shown that many of the dinoflagellate species migrate to avoid the predation of copepod and other grazer zooplankton [4,31]. Therefore, it is clear that the motile phytoplankton (dinoflagellate) and its predator zooplankton (copepod) exhibit opposite migration patterns; the zooplankton undertakes a normal DVM (up at night, down during the day), whereas the dinoflagellate undertake a reverse DVM (down at night, up during the day).…”
Section: Introductionmentioning
confidence: 99%